ANALISIS KETIMPANGAN PENDAPATAN, KEMISKINAN, DAN PERTUMBUHAN EKONOMI DI SUMATERA UTARA : SUATU TINJAUAN LITERATUR - Fridayani M. Sitio; Hanna Hotmian Br Silalahi; Hotmaria Silva Dewi Naibaho; Eko Wahyu Nugrahadi; Muammar Rinaldi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Income inequality and poverty are major problems for economic growth at both the national and regional levels. Economic growth, income inequality and poverty are prioritised to improve economic development. This study aims to determine the extent to which income inequality and poverty index affect the success of economic growth in North Sumatra. A review of 33 relevant articles from Sinta indexed journals shows that income inequality and poverty index are highly correlated with economic growth in North Sumatra. The study clearly states that higher economic growth will reduce the scale of income inequality and poverty in a region. Thus, this is a serious problem that requires special attention from the government. To overcome this problem, the government should focus on income equality. The achievement of income equality will contribute to the convenience of the community and the creation of community labour productivity. Therefore, fair and equitable income circulation can reduce social and economic problems such as poverty. With the achievement of these two indicators, it will be a huge capital in helping to achieve stable economic growth.